Biokinematic analysis of gait in patients with hemiplegia/Análisis biocinemático de la marcha en pacientes con hemiplejia - Robiel Jesús Pozo-Sánchez; Amada Plácida Gómez-Zoquez; Jacqueline Medrano-Montero; Pablo Alejandro Curay-Carrera; Darwin Manuel Abalco Farinango (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2022)
Introduction: A biokinematic analysis of gait was performed in patients with hemiplegia, which is the paralysis of one side of the body, recognized in the context of medical sciences and therapeutic physical culture as hemiplegic syndrome. Objective: It consisted of determining the biokinematic modifications that are manifested in the gait of patients with hemiplegia in the "Pedro Díaz Coello" health area of Holguín. Materials and methods: The sample consisted of five patients who received systematic care in the rehabilitation room of the health area of the " Pedro Díaz Coello" polyclinic in the municipality of Holguín. The interviews conducted with medical and physical rehabilitation personnel who work in the health area, with researchers from the Faculty of Physical Culture and Sports of the University of Holguín, the review of normative documents on multidisciplinary work and the observation of rehabilitation sessions, showed the need to address the issue from biomechanics, given the limited quantification of its indicators. In order to analyze the behavior of biokinematic indicators of pathological gait, the videographic technique was used. With the Kinovea software, in version 0.8.27, the controlled indicators were quantified. Results: Together with the qualitative study for each patient, it allowed a comparison of the characteristics of their gait with the normal pattern and the elaboration of a group of recommendations to be considered during the physical rehabilitation process. Conclusions: It was possible to analyze the behavior of the biokinematic indicators of hemiplegic gait in the patients studied, their comparison with normal gait, as well as a set of recommendations to be taken into account in the rehabilitation process